Deaminative Borylation of Aliphatic Amines Enabled by Visible Light Excitation of an Electron Donor–Acceptor Complex. Issue 65 (30th October 2018) - Sandfort, Frederik; Strieth‐Kalthoff, Felix; Klauck, Felix J. R.; James, Michael J.; Glorius, Frank
Abstract: A deaminative strategy for the borylation of aliphatic primary amines is described. Alkyl radicals derived from the single‐electron reduction of redox‐active pyridinium salts, which can be isolated or generated in situ, were borylated in a visible light‐mediated reaction with bis(catecholato)diboron. No catalyst or further additives were required. The key electron donor–acceptor complex was characterized in detail by both experimental and computational investigations. The synthetic potential of this mild protocol was demonstrated through the late‐stage functionalization of natural products and drug molecules. Abstract : Take it away : A deaminative strategy for the borylation of aliphatic amines is described. Alkyl radicals derived from redox‐active pyridinium salts were borylated in a visible light‐mediated reaction with bis(catecholato)diboron. The synthetic potential of this method was demonstrated by late‐stage functionalization of natural products and drug molecules. The key electron donor–acceptor complex is characterized in detail by various experiments as well as computational investigations.